Cognitive Level Analysis of Summative Assessments: A Basis for A Professional Development Framework for Public Secondary English Teachers in Bagabag 1 District - Mesias , Caroline; Bugnay , Eileen (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study analyzed the cognitive alignment of summative assessments in public secondary English classrooms in Bagabag I District as a basis for developing a professional development framework for teachers. Specifically, it examined the distribution of test items across the levels of the Revised Bloom’s Taxonomy, remembering, understanding, applying, analyzing, evaluating, and creating, to provide a detailed cognitive mapping and determine the extent to which higher-order thinking skills are integrated into classroom assessments. A mixed-methods design was employed, combining document analysis of summative test items with semi-structured interviews of public secondary English teachers, with data triangulation used to validate findings and examine alignment between reported practices and actual assessment content. Results revealed that assessments were largely concentrated on lower-order cognitive skills, with higher-order thinking skills significantly underrepresented. While teachers recognized the importance of cognitive alignment, they reported challenges, including limited training, time constraints, and insufficient instructional resources. Based on these findings, a professional development framework was proposed to strengthen teachers’ competencies in designing cognitively aligned assessments, thereby improving instructional effectiveness and student learning outcomes. This study contributes to the literature by offering a nuanced analysis of cognitive levels and identifying key factors influencing assessment practices. It directly supports Sustainable Development Goal 4 (Quality Education) by promoting improved assessment design and enhancing the quality of teaching and learning in secondary education.